2014
DOI: 10.1007/s13394-013-0111-6
|View full text |Cite
|
Sign up to set email alerts
|

Inquiry pedagogy to promote emerging proportional reasoning in primary students

Abstract: Proportional reasoning as the capacity to compare situations in relative (multiplicative) rather than absolute (additive) terms is an important outcome of primary school mathematics. Research suggests that students tend to see comparative situations in additive rather than multiplicative terms and this thinking can influence their capacity for proportional reasoning in later years. In this paper, excerpts from a classroom case study of a fourth-grade classroom (students aged 9) are presented as they address an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 40 publications
(37 reference statements)
2
18
0
1
Order By: Relevance
“…Furthermore, Sawatzki (2014a) argued that an effective approach to teaching financial literacy is to incorporate age-appropriate financial dilemmas that involve social, ethical and mathematical problem solving, and this was illustrated in the case we presented. Thus, we found that through group-based learning in inquiry-based mathematics lessons (see Fielding-Wells et al 2014), it was possible for students to experience age-appropriate financial dilemmas (Sawatzki 2014a) and to consider, through discussion, how their financial decisions affected others (Lucey et al 2015).…”
Section: Concluding Remarks and Implications For Future Researchmentioning
confidence: 99%
“…Furthermore, Sawatzki (2014a) argued that an effective approach to teaching financial literacy is to incorporate age-appropriate financial dilemmas that involve social, ethical and mathematical problem solving, and this was illustrated in the case we presented. Thus, we found that through group-based learning in inquiry-based mathematics lessons (see Fielding-Wells et al 2014), it was possible for students to experience age-appropriate financial dilemmas (Sawatzki 2014a) and to consider, through discussion, how their financial decisions affected others (Lucey et al 2015).…”
Section: Concluding Remarks and Implications For Future Researchmentioning
confidence: 99%
“…The teacher was able to use this discussion to encourage students with accurate conceptions and more articulately formed ideas to share with the class and thus refine their own understandings. Responses the students offered were challenged and a deeper focus on proportion, as distinct from an absolute length, was achieved (for greater discussion on the development of students' proportional reasoning in this unit, refer to Fielding-Wells, Dole, & Makar, 2014). The students determined in discussion that they would need a range of adult human proportions to contrast against Barbie and consideration was given to which measures would be appropriate for the purpose.…”
Section: Devise Phase: 2 Hoursmentioning
confidence: 99%
“…How mathematics is learnt in an inquiry setting will differ to learning mathematics in other settings. Students are required to make many decisions throughout the inquiry process involving how to proceed to solve the problem being explored (Fielding-Wells, Dole & Makar, 2014;Fielding-Wells & Makar, 2012;Makar, 2008;. The social norms and expectations established in the classroom which make the community of inquiry (Goos, 2004;Makar, 2012) will also influence how students think about mathematics as they: contemplate the ideas of others, approach tasks with a focus on creation and finding-out rather than on taught rules and procedures, respond to set-backs they encounter and analyse their own thinking to clearly communicate their ideas to others.…”
Section: Learning Mathematics In An Inquiry Classroommentioning
confidence: 99%